The Determination of Algae Group as Bioindicator of Water Quality Change Affected by Mercury Release from Artisanal Small-Scale Gold Mining (ASGM) - Herto Dwi Ariesyady; Indah Yusliga Sari Purba (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Artisanal small scale gold mining (ASGM) practices typically use mercury for amalgamation. Near water environments this can degrade water quality and aquatic biota, including algae. Changes in algal communities can reflect water environment disturbance. The aim of this study was to determine if algae can be used as bioindicator of river water quality impacted by ASGM activities. The research was conducted from July to October 2018 at thirty sampling sites along rivers near ASGM areas in several regencies of Indonesia. Composite samples of water and sediment were collected. A plankton net and brushing methods were used to collect planktonic and benthic algae, respectively. The physicochemical parameters of the water and the sediment as well as the dominant algae genera were analyzed statistically with principal component analysis. The results showed that the total mercury concentration in the water ranged from <0.04 to 20 µg.L-1, while in the sediment the maximum value was 13,500 µg.kg-1. The total mercury content in the sediment was negatively correlated with the dominant benthic Navicula at a significance level of p < 0.05. This means that a low density of benthic Navicula can be proposed as a bioindicator of water quality, indicating the increase of mercury pollution in sediment.